SINERGITAS OTAK KIRI DAN KANAN DALAM PEMBELAJARAN BIOLOGI - I Made Subrata; I Gusti Ayu Rai (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2025)
Biology is a sub-field of natural science that focuses on studying living things, including humans, animals, and plants, and their interactions with the environment. This field is based on ideas that can be felt through the use of scientific methods. In applying scientific methods in Biology learning, synergy between all parts of the brain is absolutely necessary so that learning objectives can be achieved optimally. In the brain there are three ways of thinking, namely rational intelligence, emotional intelligence and spiritual intelligence. The three intelligences are divided into two hemispheres of the brain, namely the left brain and the right brain. Learning a field of science that also implicitly must instill hard skills and soft skills, should optimize the function of all parts of the brain to express the three aspects of intelligence. The cooperative learning model is very relevant to optimizing brain function, because there is cooperation to help each other, tolerate each other, and motivate each other so that harmony is created. The humanities aspect in learning also needs to be created. The learning environment also needs to be attempted to create a relaxed, friendly and enjoyable learning situation to be able to optimize the function of the right brain to support the work of the left brain in processing learning materials